Aprovechamiento del suero ácido de queso doble crema para la elaboración de quesillo utilizando tres métodos de complementación de acidez con tres ácidos orgánicos (2006)
ABSTRACT: Quesillo is a kind of cheese made with the acid serum of double cream cheese. General objective: To make quesillo with the acid serum of double cream cheese in a short period of time. Specific objectives: to evaluate three methods of acidity complementation with organic acids (lactic, citric, and acetic) making quesillo, To asses the sensory, physicochemical and texture characteristics of quesillo. Dependent variables: taste, texture, fat, protein, and efficiency. Factor: cheese, treatment: 3; repetitions: 9. Methods: The ‘quesillo’ was made with milk, double cream cheese acid serum, and different organic acids (lactic, citric, and acetic). Each acid was used for three times in the process. The final product was assessed for sensory, physicochemical and texture characteristics and statistical tests of variance analysis was applied. Materials: milk, serum from double cream cheese, salt, rennet. Results: there were not significant differences between treatments; confidence level was 95 %, p >0.05, Conclusion: Quesillo was made with high quality proteins and fat, in a short period of time, using double cream cheese serum this method could benefit the economics and the environment.